Stigma Toward Men Who Have Sex with Men Among Future Healthcare Providers in Malaysia: Would More Interpersonal Contact Reduce Prejudice? - Earnshaw, Valerie A. (AIDS Behav, 2016)
Men who have sex with men (MSM) living in countries with strong stigma toward MSM are vulnerable to HIV and experience significant barriers to HIV care. Research is needed to inform interventions to reduce stigma toward MSM in these countries, particularly among healthcare providers. A cross-sectional survey of 1158 medical and dental students was conducted at seven Malaysian universities in 2012. Multivariate analyses of variance suggest that students who had interpersonal contact with MSM were less prejudiced toward and had lower intentions to discriminate against MSM. Path analyses with bootstrapping suggest stereotypes and fear mediate associations between contact with prejudice and discrimination. Intervention strategies to reduce MSM stigma among healthcare providers in Malaysia and other countries with strong stigma toward MSM may include facilitating opportunities for direct, in-person or indirect, media-based prosocial contact between medical and dental students with MSM.